2007
DOI: 10.1073/pnas.0705368104
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline, an α4β2 nicotinic acetylcholine receptor partial agonist, selectively decreases ethanol consumption and seeking

Abstract: Alcohol dependence is a disease that impacts millions of individuals worldwide. There has been some progress with pharmacotherapy for alcohol-dependent individuals; however, there remains a critical need for the development of novel and additional therapeutic approaches. Alcohol and nicotine are commonly abused together, and there is evidence that neuronal nicotinic acetylcholine receptors (nAChRs) play a role in both alcohol and nicotine dependence. Varenicline, a partial agonist at the ␣4␤2 nAChRs, reduces n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
370
13
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(416 citation statements)
references
References 55 publications
26
370
13
4
Order By: Relevance
“…Further evidence is provided in recent animal studies of varenicline, an alpha4-beta2 nicotinic receptor partial agonist used in smoking cessation. This drug reduces not only nicotine dependence, but also alcohol consumption in rats (Steensland et al, 2007). Hendrickson et al (2010) showed this effect depends specifically on activation of alpha4 nicotinic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence is provided in recent animal studies of varenicline, an alpha4-beta2 nicotinic receptor partial agonist used in smoking cessation. This drug reduces not only nicotine dependence, but also alcohol consumption in rats (Steensland et al, 2007). Hendrickson et al (2010) showed this effect depends specifically on activation of alpha4 nicotinic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these subtypes also mediate the rewarding properties of alcohol, alcohol cues as well as alcohol intake in rodents (Ericson et al 2009;Jerlhag et al 2006b;Larsson and Engel 2004;Löf et al 2007;Steensland et al 2007). These data are verified in clinical tests; thus blocking these subtypes, by using varenicline, reduces the intake of alcohol in heavy drinking smokers (McKee et al 2009) and one haplotype of the 6* gene is associated with heavy alcohol use ).…”
Section: The Central Ghrelin Signalling System Integrates With a Key mentioning
confidence: 96%
“…We also showed that chlorzoxazone, an FDA-approved SK activator used for decades as a centrally acting myorelaxant, significantly reduces excessive alcohol intake in rats with intermittent access to ethanol, but does not reduce the more moderate alcohol intake in rats with continuous access to alcohol (Hopf et al, 2011). Alcohol intake in intermittent-access rats shows a number of other features, which have been considered to perhaps model some aspects of human alcoholism, including escalation of intake, sensitivity to compounds that reduce alcohol intake in human alcoholics (Steensland et al, 2007; Novel therapeutic strategies for addiction G Addolorato et al ............................................................................................................................................................... Simms et al, 2008;McKee et al, 2009) and aversion-resistant and perhaps compulsive alcohol intake (Hopf et al, 2010b). Thus, the SK activator chlorzoxazone may represent a potent and immediately accessible treatment for human alcoholism.…”
Section: Sk-type Calcium-activated Potassium Channelsmentioning
confidence: 99%